RANCANG BANGUN POMPA AIR SISTEM AKSIAL - Zelimkhan Yanderbiyev Alatas; Rianto Wibowo; Sugeng Slamet (JURNAL CRANKSHAFT, 2022)
The pump is a very important tool for various necessities of life, including fish farming activities. The selection of the wrong type of pump can result in large costs, so knowledge and skills are needed about pumps and their use. The background of the research is the need for the type of pump that is in accordance with the conditions in the field, especially for the use of fish farming. The initial step of this research is the calculation of the pump dimensions, followed by the fabrication process / component manufacture according to the calculations that have been done. The final stage of the research is the assembly and testing process. The calculation phase results in the dimensions of the pump with an impeller diameter of 45.9 mm and a hub diameter of 21.5 mm, as well as a number of 8 blades. The pump will operate at 1200 rpm with a flow rate of 42 liters/minute with a max head height of 1.2 meters. In the final stage of testing, the pump operates with a flowrate of 40 L/m and a maximum head of 1 meter. The actual discharge and head of the pump are different from the design value caused by the impeller dimensions that are still not suitable, causing the pump head to drop